The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2516/ogst/2013203
|View full text |Cite
|
Sign up to set email alerts
|

Automotive Catalyst State Diagnosis Using Microwaves

Abstract: -The state of catalysts plays a key role in automotive exhaust gas aftertreatment. The soot or ash loading of Diesel particulate filters, the oxygen loading degree in three-way catalysts, the amount of stored ammonia in SCR catalysts, or the NO x loading degree in NO x storage catalysts are important parameters that are today determined indirectly and in a model-based manner with gas sensors installed upstream and/or downstream of the catalysts. This contribution gives an overview on a novel approach to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The wideband lambda probes or other exhaust gas sensors are also for research purposes only. Modified from [13]. Table 2 with C3H8 for detailed gas compositions.…”
Section: The Microwave Cavity Perturbation Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The wideband lambda probes or other exhaust gas sensors are also for research purposes only. Modified from [13]. Table 2 with C3H8 for detailed gas compositions.…”
Section: The Microwave Cavity Perturbation Techniquementioning
confidence: 99%
“…A typical general setup is shown in Fig. 1 (from [13]). The cavity resonator may be coupled to a source and a load via simple "antennas" (e.g.…”
Section: The Microwave Cavity Perturbation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Studies with a combined system of a TWC-coated GPF on an engine dynamometer proved the system functionality under transient conditions within the European driving cycle (NEDC) [ 30 ]. In NO x reduction application, the storage state of lean NO x traps (LNT) was successfully monitored, but application to this catalyst type seems to suffer from a comparably small signal [ 32 , 33 ]. The potential of the RF technique to determine the NH 3 storage on SCR catalysts is presumed and is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…More details on the microwave-based technique for catalyst monitoring can be found in Refs. [35][36][37][38]. For the studies reported in this text, only the magnitude of the reflection parameter, |S 11 | (plotted in dB;…”
Section: Experimental Setups and Preliminary Testsmentioning
confidence: 99%